Optimal velocity estimation model based on non-differential Doppler observations from BDS-3 satellites - Zejie WANG; Qianxin WANG; Tianwen SHANG (Dianxin kexue)
An optimized velocimetric model based on non-differential Doppler observations from BDS-3 satellites with high accuracy and low model complexity was proposed to address insufficient accuracy and low efficiency of velocity estimation method.The observation data from BDS-3 satellites was used to estimate the carrier velocity by using Doppler velocimetric model with low complexity.In order to improve velocity estimation accuracy and solving efficiency, firstly, the model was linearized, and then loose constraints was added based on the correlation between the carrier heading and its velocity vector.The velocity measurement accuracy of the model was verified with field-collected BDS-3 observations, and the applicability of the model was evaluated.The experimental results show that: when the carrier is stationary, the optimized Doppler velocimetry accuracy can reach cm/s or even mm/s level, and in the comparison with the original Doppler velocimetry, the horizontal velocity accuracy was improved by about 60% and the solution time was shortened by 24%;when the carrier is moving, the Doppler velocimetry accuracy with heading constraints can be improved by 14% ~ 21% in north and east compared with the original Doppler velocimetry, and the solution time was improved by about 20%.